2003
DOI: 10.1029/2002ja009663
|View full text |Cite
|
Sign up to set email alerts
|

In situ Polar observation of transverse cold‐ion acceleration: Evidence that electric field generation is a hot‐ion finite gyroradii effect

Abstract: [1] Recent results with the Polar TIMAS instrument (ion mass spectrometer) have revealed that earthward magnetic field-aligned and velocity-dispersed flows of 1-to 33-keV protons (and other ions) from the outer magnetosphere are inherently ''blast-like'' and exhibit a complex filamentary structure where transverse scale sizes may often be a few proton gyroradii. These velocity-dispersed protons (and accompanying hot electrons) have been found to have a close association with enhanced large pitch angle outflow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…A similar association of enhanced large pitch angle ion outflow and velocity-dispersed ions was recently reported in a Polar-spacecraft-based study at distances of 6 Re and higher (Lennartsson, 2003). In addition, here we found that the enhanced conical outflow coincided with the edges (boundaries) of energetic magnetotail ion beamlets.…”
Section: Generation Of Ion Conicssupporting
confidence: 64%
See 1 more Smart Citation
“…A similar association of enhanced large pitch angle ion outflow and velocity-dispersed ions was recently reported in a Polar-spacecraft-based study at distances of 6 Re and higher (Lennartsson, 2003). In addition, here we found that the enhanced conical outflow coincided with the edges (boundaries) of energetic magnetotail ion beamlets.…”
Section: Generation Of Ion Conicssupporting
confidence: 64%
“…Some observational evidence has been reported that ion beams could lead to broadband electrostatic noise (BEN) (e.g., Gurnet et al, 1976;Grabbe and Eastman, 1984) via beam-related instabilities. Magnetotail ion beams have been invoked for the acceleration and heating of ionospheric ion outflow to form ion beams and conics, respectively (Alfvén and Fälthammar, 1963;Schriver et al, 2003;Lennartsson, 2003;Janhunen et al, 2003). Furthermore, Elphinstone et al (1995) associated velocity-dispersed ion structures (VDIS) with the double oval, and Janhunen et al (2003) suggested that the free energy associated with ion shell distributions in the PSBL could lead in a sequence of events to the acceleration of auroral electrons causing auroral arcs.…”
Section: Introductionmentioning
confidence: 99%
“…Under more normal and near-steady conditions the centrifugal acceleration is not expected to generate keV energies until the ions reach the strongly curved portion of field lines at the tail midplane [see Cladis, 1986, Figure 2; see also Delcourt et al, 1988Delcourt et al, , 1989. Furthermore, this mechanism by itself generates field-aligned velocity distributions, whereas the TIMAS observations very often show broad pitch angle distributions of up-flowing ions at all altitudes [Lennartsson, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Such a mechanism may involve both transverse ion acceleration, creating ''newly born conics'' in the parlance of Miyake et al [1993], and the parallel kind. A random-type, narrow-scale (filaments) mechanism to fit that mold is outlined by Lennartsson [2003], although its specific purpose is to help explain the collocation of transversely accelerated H + , He + , and O + ions with transient bursts of hot H + ions from the near-midnight tail, rather than with cusp ion bursts. This mechanism would be powered by the kinetic energy flux associated with the H + bursts (and with accompanying electrons).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation